ANALISIS PEMASARAN JAGUNG (Zae mays L.) DI DESA KARANGMALANG KECAMATAN KEDUNGBANTENG KABUPATEN TEGAL - Dian Bintang Pamungkas; Pujiharto Pujiharto; Watemin Watemin (Universitas Muhammadiyah Purwokerto, 2016)
The purpose of the research are to determine the pattern of corn marketing channel, the farmer share and margin of knowing the marketing of corn, the farmer knowing the difference of value farmer share and marketing margin of corn and he knowing the problems faced by farmers at the marketing of corn in Karangmalang village, Kedungbanteng Sub District, Tegal. The research used survey method. The study was conducted in Karangmalang village, Kedungbanteng Sub District, Tegal. The respondents taking use simple random sampling method and determined amounted to 120 farmers of corn, 3 merchant wholesalers, and 2 retailers. The study was conducted from February to December 2015. The results showing there are two patterns of marketing channels. The first marketing channel share of 91.66 percent and the second marketing channel by 96.55 per cent, the margins of the first marketing channel Rp.250,-/kg and the second marketing channel Rp.100,-/kg. Any the differences of farmers share and margins in the marketing of maize. The Problems faced by farmers in the marketing of corn there is the problem of payment of corn, the corn growers who sell to wholesalers not directly get the money. So that farmers find it difficult to play the capital for the next planting season.